Atomic Structure and Chemical Elements (Islamic Perspective) Book as a Learning Resource - Siska Oktapianti (Interdisciplinary Explorations in Research Journal, 2024)
This research is a detailed examination of the development of the chemistry educational sources. The aims of the research are to describe (1) the validity of teaching material (2) the students' responses to the teaching material developed. The type of research is research and development (R&D), with model 4D by Thiagarajan. The stages development of 4D  are   define, design, develop and  desseminate. The subjects of this study are students and lecturers of UIN Antasari. The data collection techniques and instruments used in this study are interview guides, questionnaires and observations. Based on the results of expert validation: validation of material experts with an average of 81% with the criteria "Very Valid" and validation of media experts with an average of 83.4% with the criteria "Very Valid" state that the teaching material developed is very valid and is suitable as teaching material. The percentage score of 91.6% with the "Very Good" criteria is obtained from the responses of 10 chemistry education students of UIN Antasari Banjarmasin to the teaching material developed. This book can be used in learning process that involves both students and lecturers.  Keywords : Atomic Structure , Islamic Perspective, Self Learning Resource